Detection and phylogenetic characterization of human hepatitis E virus strains, Czech Republic - Vasickova, Petra; Slany, Michal; Chalupa, Pavel; Holub, Michal; Svoboda, Radek; Pavlik, Ivo (Emerging infectious diseases, 2011)
To determine the origin of hepatitis E virus in the Czech Republic, we analyzed patient clinical samples. Five isolates of genotypes 3e, 3f, and 3g were obtained. Their genetic relatedness with Czech strains from domestic pigs and wild boars and patient recollections suggest an autochthonous source likely linked to consumption of contaminated pork.
Keywords: RNA, Viral; Feces; RNA virová; Male; Genotype; fylogeneze; Česká republika; feces; Phylogeny; Hepatitis E virus; molekulární sekvence - údaje; Adult; Aged; dospělí; mužské pohlaví; senioři; Czech Republic; virus hepatitidy E; lidé; ženské pohlaví; otevřené čtecí rámce; Humans; hepatitida E; Open Reading Frames; genotyp; Molecular Sequence Data; Female; Hepatitis E; lidé středního věku; Middle Aged